Changes in the functional state of the endothelium in conditions of experimental rhegmatogenous retinal detachment and its correction - I. M. Levytskyi; I. V. Savytskyi; G. V. Levytska; I. V. Miastkivska (Kazimierz Wielki University, 2017)
RRD - photoreceptors detachment from retinal pigment epithelial by retrovitreal fluid, which penetrates through the breakdown of the neurosensory part. Purpose: investigation of endothelial dysfunction in rhegmatogenous retinal detachment pathogenesis and analysis of correction methods effectiveness. Von Willebrand factor (VWF) is common marker of endothelial dysfunction. It was established increase in its level in the 7th day of the research in all groups in which rats were modeled rhegmatogenous retinal detachment. Differences in the comparison of these groups among themselves have not been identified. At 14th day, it is observed endothelial dysfunction development in group 2 (differences in comparison with the data of intact animals already at the level of significance p